Answer: x = - 3.5
Step-by-step explanation:
Rewrite the equation by completing the square.
4x2 + 28x + 49 = 0
Completing the square method :
Divide through by the Coefficient of x^2
x^2 + 7x + (49/4) = 0
a = 1, b = 7, c = 49/4
Move c to the right side of the equation
x^2 + 7x = - 49/4
Complete the square on the left hand side by squaring its half of the x term
(7/2)^2 = (49/4)
Add the output to both sides of the equation
x^2 + 7x + (49/4) = - (49/4) + (49/4)
(x + 7/2)^2 = 0
Square root of both sides
x + 7/2 = 0
x = - 7/2
x = - 3.5
HOPE THIS HELPS YOU..... :)
Answer:
as the cycle continues, you will always get 50 as the answer, since you are dividing both the numerator and the denominator with 10 in each expression. In other words, the 10:00 you divide the numerator which cancels out with the 10 you divide the denominator with. So the answer will always be 50 in each next expression.
Step-by-step explanation:
(I) 45÷90= 4500/90 = 50
(ii) 450÷9= 450/9 =50
(iii) 45÷0.9 = 45/0.9=50
(iv) 4.5 ÷ 0.09 = 45/0.09
starting with (I) 4500÷90 = 4500/90 =50
you divide the numerator and the denominator by 10 to get ; (ii) 450÷9 = 450/9 = 50
as the cycle continues you will always get 50 as the answer since you are dividing both the numerator and the denominator with 10 in each expression. In other words, the 10:00 you divide the numerator with cancels out with the 10 you divide the denominator with. So the answer will always be 50.